Yacon (Smallanthus sonchifolius) use as an antioxidant in diabetes - Ferraz, Ana Paula Costa Rodrigues [UNESP]; Garcia, Jéssica Leite [UNESP]; Costa, Mariane Róvero [UNESP]; De Almeida, Carol Cristina Vágula [UNESP]; Gregolin, Cristina Schimitt; Alves, Pedro Henrique Rizzi [UNESP]; Hasimoto, Fabiana Kurokawa [UNESP]; Berchieri-Ronchi, Carolina B. [UNESP]; Santos, Klinsmann Carolodos; Corrêa, Camila Renata [UNESP] (Elsevier, 2020)
Diabetes mellitus is a complex disease characterized by glucose, lipid, and protein deregulated metabolism due to insulin deprivation affecting various tissues in the human body. Dysmetabolism in diabetes could lead to oxidative stress, which, in turn, could contribute to pathological processes in the diabetic condition. Natural compounds have been recognized as potential natural sources for diabetes prevention, management, and treatment. Yacon (Smallanthus sonchifolius), belonging to the Asteraceae family, is an indigean perennial herbaceous plant native to the Andes mountains, and is rich in polyphenols and bioactive compounds. Several studies have attributed antioxidant and antidiabetogenic effects to yacon. For these reasons, this chapter aims to elucidate the effects of yacon on diabetic-related complications based on its phytochemical profile. First, the diabetes condition and how antioxidants, in general terms, could act are described. Further, yacon is described in its most important approaches and, finally, its phytochemical profile and interactions on diabetes are discussed.
Keywords: Antioxidants; Diabetes; Phytochemical profile; Polyphenols; Yacon